KONTRIBUSI UPACARA ADAT MENDIRIKAN DAN PINDAH RUMAH TERHADAP NILAI PENDIDIKAN ISLAM - Moh. Haitami Salim (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2013)
There are so many kinds of traditional ceremonies among Pontianak Malay community performed along their life cycle. All the traditional ceremonies need a specific properties according to the kinds of ceremony performed by the performer. Each of the property as well as the steps of the ceremony had a specific symbol denoted to specific meaning. One of the traditional ceremony commonly performed by the community of Pontianak Malay is traditional ceremony of building and moving house that had so deep educational values.